IMPACT OF GLOBAL FINANCIAL CRISIS ON JAPAN, CHINA, INDIA AND USA STOCK EXCHANGE AND INTER-LINKAGE BETWEEN THEM - Najaf, Rabia (International Journal of Research -GRANTHAALAYAH, 2016)
In this paper, we analyzed the impact of financial crisis on different countries by the using of E-GARCH model .our main finding is that in the financial crisis has impact on the stock exchange of different countries. We proved that due to financial crisis most of countries stock exchange have been affected badly. In the world,the American stock exchange was established in 1792. Two dozen brokers were started the stock trading.Now a day, 2,429 companies are listed under this stock exchange. The prime objective of the scholars is to find out the impact of financial crisis on the different stock market. Scholars have proved that financial crisis have always impacted on the financial markets.